Main Directions of Improvement of Elements of Marketing Mix in "SAG" LLC - Azimovna, Musayeva Shaira; Shokhrukhovich, Usmanov Farzod; Alamovna, Muminova Farangiz (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
In this article, students will learn how to evaluate economic activity, conclude contracts related to foreign economic activity, choose partners, use international marketing principles in their activities, make decisions based on them, increase production efficiency, be competitive in the world market. Production of products is a powerful factor, and export opportunities are considered.